Socioecological correlates of clinical signs in two communities of wild chimpanzees (Pan troglodytes) at Gombe National Park, Tanzania. Issue 1 (16th May 2016) - Lonsdorf, Elizabeth V.; Gillespie, Thomas R.; Wolf, Tiffany M.; Lipende, Iddi; Raphael, Jane; Bakuza, Jared; Murray, Carson M.; Wilson, Michael L.; Kamenya, Shadrack; Mjungu, Deus; Collins, D. Anthony; Gilby, Ian C.; et al.
Abstract : Disease and other health hazards pose serious threats to the persistence of wild ape populations. The total chimpanzee population at Gombe National Park, Tanzania, has declined from an estimated 120 to 150 individuals in the 1960's to around 100 individuals by the end of 2013, with death associated with observable signs of disease as the leading cause of mortality. In 2004, we began a non‐invasive health‐monitoring program in the two habituated communities in the park (Kasekela and Mitumba) with the aim of understanding the prevalence of health issues in the population, and identifying the presence and impacts of various pathogens. Here we present prospectively collected data on clinical signs (observable changes in health) in the chimpanzees of the Kasekela ( n  = 81) and Mitumba ( n  = 32) communities over an 8‐year period (2005–2012). First, we take a population approach and analyze prevalence of clinical signs in five different categories: gastrointestinal system (diarrhea), body condition (estimated weight loss), respiratory system (coughing, sneezing etc.), wounds/lameness, and dermatologic issues by year, month, and community membership. Mean monthly prevalence of each clinical sign per community varied, but typically affected <10% of observed individuals. Secondly, we analyze the presence of clinical signs in these categories as they relate to individual demographic and social factors (age, sex, and dominance rank) and simian immunodeficiency virus (SIVcpz) infection status. Adults have higher odds of being observed with diarrhea, loss of body condition, and wounds or lameness when compared to immatures, while males have a higher probability of being observed with wounds or lameness than females. In contrast, signs of respiratory illness appear not to be related to chimpanzee‐specific factors and skin abnormalities are very rare. For a subset of known‐rank individuals, dominance rank predicts the probability of wounding/lameness in adult males, but does not predict any adverse clinical signs in adult females. Instead, adult females with SIVcpz infection are more likely to be observed with diarrhea, a finding that warrants further investigation. Comparable data are needed from other sites to determine whether the prevalence of clinical signs we observe are relatively high or low, as well as to more fully understand the factors influencing health of wild apes at both the population and individual level. Am. J. Primatol. 80:e22562, 2018. © 2016 Wiley Periodicals, Inc.